La función identificadora del lenguaje - Patiño Rosselli, Carlos (Enunciación, 2004)
This article deals about, firstly, currents of thought and figures of linguistics whose works emphasize the "identifying function" of language. Particular attention is given to the "idealist school" that flourished in Germany. This article also examines, the way in which this function appears in social and linguistic phenomena of different societies, including the Colombian one.